2017
DOI: 10.1016/j.bmcl.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, SAR and molecular docking study of novel non-β-lactam inhibitors of TEM type β-lactamase

Abstract: The novel classes of acylated phenoxyanilide and thiourea compounds were investigated for their ability to inhibit TEM type β-lactamase enzyme. Two compounds 4g and 5c reveal the inhibition potency in micromolar range and show their action by non-covalent binding in the vicinity of the TEM-171 active site. The structure activity relationship around carbon chain length and different substituents in ortho- and para-positions of acylated phenoxyanilide as well as molecular modelling study has been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A new direction involves searching for structural analogues of known βL inhibitors, including allosteric ones. The computational ligand-based in silico screening technique, in combination with molecular docking and experimental studies of βL inhibition, has been applied for the identification of acylated phenoxyaniline and thiourea compounds as novel non-β-lactam inhibitors of TEM-type βLs [11,80]. An analysis of the residues involved in the binding of the inhibitor at the active site of the enzyme showed that some of them are conservative for class A βLs, which can be prospective for inhibitors of these enzymes.…”
Section: Current Approaches For Overcoming the Resistance Conferred Bmentioning
confidence: 99%
“…A new direction involves searching for structural analogues of known βL inhibitors, including allosteric ones. The computational ligand-based in silico screening technique, in combination with molecular docking and experimental studies of βL inhibition, has been applied for the identification of acylated phenoxyaniline and thiourea compounds as novel non-β-lactam inhibitors of TEM-type βLs [11,80]. An analysis of the residues involved in the binding of the inhibitor at the active site of the enzyme showed that some of them are conservative for class A βLs, which can be prospective for inhibitors of these enzymes.…”
Section: Current Approaches For Overcoming the Resistance Conferred Bmentioning
confidence: 99%
“…Furthermore, the presence of the pyrazole nucleus in different structures leads to diversified applications in different areas such as technology, medicine, and agriculture. Furthermore, pyrazole derivatives have arrived an extensive view of researchers through the past few decades due to their highly reactive effects as anti-inflammatory 3 , antiglaucoma 4 , antiviral 5 , antimicrobial 6 , antidiabetic activities 7 . In addition, pyrazole prodrugs have been recorded to maintain significant anticancer activity 8 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial resistance is spreading globally and poses a serious threat to human health (Liscio et al, 2015) β-lactam resistance has accelerated to an uncontrolled rate due to many reasons like increased consumption, poor prescribing strategies, and abuse of the antibiotics to treat minor infections etc (Liscio et al, 2015). The most significant form of resistance is the generation of β-lactamases enzyme by the pathogenic bacteria which destroy the β-lactam ring which is essential for antibacterial activity (Blizzard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As TEM-class b-lactamase inhibitors, Antipin et al (2017) synthesised new modules of acylated phenoxyanilide and thiourea compounds and tested them for their capacity to block TEM type -lactamase enzyme (Antipin et al, 2017). IID572, a novel broad spectrum BLI of the diazabicyclooctane (DBO) family that was synthesised by Reck et al, 2019, has the ability to revive piperacillin's antibacterial activity against piperacillin/tazobactam-resistant clinical isolates.…”
Section: Introductionmentioning
confidence: 99%